Monitoring TGFβ signaling in irradiated tumors - Ma, Lin; Gonzalez-Junca, Alba; Chou, William; Barcellos-Hoff, Mary Helen (Methods in cell biology, 2023)
Transforming growth factor β (TGFβ) is exquisitely regulated under physiological conditions but its activity is highly dysregulated in cancer. All cells make TGFβ and have receptors for the ligand, which is sequestered in the extracellular matrix in a latent form. Ionizing radiation elicits rapid release of TGFβ from these stores, so-called activation, over a wide range of doses and exposures, including low dose (<1Gy) whole-body irradiation, creating an extraordinarily potent signal in the irradiated tissue or tumor. Hence, accurate evaluation of TGFβ activity is complicated because of its ubiquitous distribution as a latent complex. Here we describe conditions for assays that reveal TGFβ activity in situ using either tissue preparations or functional imaging.